Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1002/mrc.2086
|View full text |Cite
|
Sign up to set email alerts
|

Solid state NMR characterization of individual compounds and solid solutions formed in Sc2O3V2O5Nb2O5Ta2O5 system

Abstract: In this study, (51)V, (45)Sc and (93)Nb MAS NMR combined with satellite transition spectroscopy analysis were used to characterize the complex solid mixtures: VNb(9(1-x))Ta(9x)O(25), ScNb((1-x))Ta(x)O(4) and ScNb(2(1-x))Ta(2x)VO(9) (x = 0, 0.3, 0.5, 0.7, 1.0). This led us to describe the structures of Sc and V sites. The conclusions were based on accurate values for (51)V quadrupole coupling and chemical shift tensors obtained with (51)V MAS NMR/SATRAS for VNb(9)O(25), VTa(9)O(25) and ScVO(4). The (45)Sc NMR p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, the large convoluted quadrupolar ( C Q ) and chemical shift anisotropy (CSA) contributions to these line widths often lead to a significant broadening of the central transition resonance, even at very high magnetic field strengths. These complex characteristics describing the 93 Nb static line width often reduce the effectiveness of fast MAS rates when attempting to determine accurate values of the 93 Nb NMR parameters. , Octahedrally coordinated NbO 6 environments are normally observed to exhibit δ iso values in the range of ∼−900 to – 1100 ppm, with quadrupole coupling constants ( C Q ) typically ranging from 0 to ∼55 MHz. Four-coordinate NbO 4 and five-coordinate NbO 5 positions generally possess lower point symmetry and are characterized by more downfield δ iso values in the range of ∼−700 to – 850 ppm and very large C Q values of >80 MHz. ,, The tendency for NbO 4 to assume the reduced Nb 4+ oxidation state can result in signals which are influenced significantly by paramagnetic broadening and associated paramagnetic shifts …”
Section: Results and Discussionmentioning
confidence: 99%
“…However, the large convoluted quadrupolar ( C Q ) and chemical shift anisotropy (CSA) contributions to these line widths often lead to a significant broadening of the central transition resonance, even at very high magnetic field strengths. These complex characteristics describing the 93 Nb static line width often reduce the effectiveness of fast MAS rates when attempting to determine accurate values of the 93 Nb NMR parameters. , Octahedrally coordinated NbO 6 environments are normally observed to exhibit δ iso values in the range of ∼−900 to – 1100 ppm, with quadrupole coupling constants ( C Q ) typically ranging from 0 to ∼55 MHz. Four-coordinate NbO 4 and five-coordinate NbO 5 positions generally possess lower point symmetry and are characterized by more downfield δ iso values in the range of ∼−700 to – 850 ppm and very large C Q values of >80 MHz. ,, The tendency for NbO 4 to assume the reduced Nb 4+ oxidation state can result in signals which are influenced significantly by paramagnetic broadening and associated paramagnetic shifts …”
Section: Results and Discussionmentioning
confidence: 99%
“…2, show two main types of vanadium environments, corresponding to broad lines at 225 ppm and -245 ppm vs. reference. The signal at 225 ppm is attributed to distorted octahedral vanadium (VO 5 +1 ) which is characteristic of the V 2 O 5 layered structure [14]. The feature at -245 ppm corresponds to isolated tetrahedra of VO 4 which are found in the NbVO 5 structure [15].…”
Section: Fig 1 X-ray Diffractograms Of Nb 2x V 2-2x O 5 Powders Annea...mentioning
confidence: 99%
“…Recently, a number of solidstate NMR studies has been published involving nuclei with spin I = 7/2, such as 43 Ca [4][5][6], 45 Sc [7][8][9], 49 Ti [10][11][12], 51 V [13][14][15], 139 La [16,17], or a combination of these isotopes [18]. The purpose of such studies is to determine the chemical shift and the quadrupolar interaction parameters, and to correlate them to structure and properties of the compounds under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that application of SW-FAM sequences results in considerable improvement of the signal-to-noise ratio, which directly translates into time saving when acquisition of NMR spectra of spin-7/2 nuclei is required, as in the studies in Refs. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%